Artists and Art in Society: Creative Work for Social Change - Rallos-Lavides , Joyne Liz (My University, 2009)
Abstract: How can artists uphold their creative autonomy from the dictates of capitalism without compromising their vision for social change? Max Weber made it clear that the capitalism of to-day, which has to dominate economic life, educates and selects the economic subjects which needs through a process of economic survival of the fittest. (Weber, 1958) Eleven visual artists from the Golden Horseshoe Area and the Greater Toronto Area participated in this qualitative study and provided in-depth interviews their creative work, personal struggles and insights about the current state arts community. The data suggests connections between 'starving artists' and creative autonomy. On one hand, artists who pursued their art outside the formal art market deemed they had greater autonomy but experienced greater economic insecurity and social isolation. On the other hand, artists who practiced their art within the formal art market believed they had better freedom but needed to compromise creative autonomy and their vision for social change. On the whole, both art practices seemed to have lead artists to assume the concept of Art for 'my sake,' an assertion of their self-directed will for their own purpose, reducing artists' creative motivation to produce art society and for social change. While it may be solitary, it may also be a revolutionary strategy that enhances more control and focus on the artists' rather than pursuing society for validation and economic rewards.
Keywords: Max Weber; capitalism; economics; starving artists